Characterization of Pedagogical Knowledge: A Study of Novice Teachers - Almonacid-Fierro, Alejandro (2014)
Pedagogical knowledge, understood as a specific display of paradigmatic and ideological narratives and configurations about the character and sense of the educational action, is ultimately what each teacher defines as the learning environment. Therefore, its characterization and categorization become a central concept of scientific and pedagogical knowledge. The main objective of this article was to investigate, describe and interpret the relationship between the practice shown in the classroom and the pedagogical knowledge from the teacher-learner relationship in novice teachers graduated from the School of Education of Universidad Autónoma de Chile. A qualitative research approach was used, based on the epistemological perspective of an interpretative paradigm, utilizing the subjective comprehension of the process. Participants emphasized the importance of practical experience as fundamental in their teacher training. In addition, they see positively the emphasis given by Universidad Autónoma de Chile on forming reflective, critical and autonomous teachers through a teaching practice focused on the co-construction of knowledge.